Enhancing Reading Culture in Nigerian TVET Institutions: Institutionalizing Structured Library-Based Reading Sessions for Academic Improvement - Olayemi Tosin Ajayi; Lambert A. Ihebuzor (Yayasan Abdurrauf Cendekia Nusantara, 2026)
This study investigates the effectiveness of structured, library-based weekly reading sessions as a mechanism for improving reading culture and academic performance among students in Nigerian Technical and Vocational Education and Training (TVET) institutions. Using a mixed-methods longitudinal design, data were collected from 133 National Diploma students through self-reported survey responses, interviews, focus group discussions, and academic records. The intervention consisted of mandatory one-hour weekly reading sessions conducted in the institutional library over one academic session. Findings revealed that 85% of participants reported increased reading engagement, 72% improved motivation, and 65% enhanced comprehension. Academic performance improved significantly, with mean GPA increasing from 2.45 to 2.95, supported by paired sample t-test results (p < .001). Qualitative findings further revealed that structured environments, peer interaction, and accountability mechanisms contributed to sustained reading habits. The study concludes that structured reading sessions represent a viable and scalable institutional strategy for strengthening reading culture in TVET contexts. Policy implications include curriculum integration of reading programs, improved library infrastructure, and interventions to manage digital distractions.